Empowering Students in the Digital Era: An Analysis of Interactive E-Modules' Effect on Digital Mathematical Communication - Weylin; Raharjo, Hendri; Haqq, Arif Abdul; Larsari, Vahid Norouzi (International Journal of Mathematics and Mathematics Education (IJMME), 2023)
Students' mathematical digital communication abilities are paramount in the current digital era, yet many continue encountering difficulties. This study focuses on using interactive e-modules as an innovative learning medium to enhance these abilities. Adopting a quantitative experimental approach, this research involved grade 8students from SMP Negeri 1 Ciwaringin during the 2022/2023 academic year, allocating them into control and experimental groups. The study aimed to evaluate student responses to the e-module, compare students' mathematical digital communication abilities before and after the module's implementation, and determine the effectiveness of the e-module. The study's results showed a significant improvement in students' abilities, with a 75.5% positive response to the e-module and an average student score increase from 36.63 (pretest) to 72.56 (posttest). An N-Gain rise of 56.62% demonstrated the effectiveness of the e-module. These findings solidify the interactive e-module as a suitable learning medium that increases student enthusiasm and participation in mathematical learning. Thus, this research significantly contributes to mathematics education, demonstrating that interactive e-modules can effectively overcome challenges in teaching mathematical digital communication.